Case report: Mexiletine suppresses ventricular arrhythmias in Andersen-Tawil syndrome - Yang, Jing; Li, Kun; Lv, Tingting; Xie, Ying; Liu, Fang; Zhang, Ping (Frontiers in Cardiovascular Medicine, 2022)
It is arduous to determine clinical solutions for Andersen-Tawil syndrome(ATS) patients intolerant of β-blocker. Here, we present the case of a 7-year-old boy with periodic paralysis and dysmorphic features who experienced syncope four times during exercise. His ECG revealed enlarged U waves and QU-prolongation associated with ATS-specific U wave patterns, frequent PVCs, and non-sustained bidirectional or polymorphic ventricular tachycardia. The genetic test showed a de novo missense mutation R218W of KCNJ2. With the diagnosis of ATS and the intolerance of β-blocker, the patient was prescribed oral medications of mexiletine 450mg/day without severe adverse effects. Repeated ECG showed decreased PVCs burden from 38% to 3% and absence of ventricular tachycardia. He remained symptom-free over two years of outpatient follow-up. This case demonstrates a new antiarrhythmic therapy with mexiletine for the prevention of life-threatening cardiac events in patients with ATS who are intolerant of β-blocker treatment.